Geological aspects on the sustainability of ancient aqueducts of Athens - Chiotis, E. D.; Marinos, P. G. (Bulletin of the Geological Society of Greece, 2012)
Geological aspects of the ancient aqueducts of Athens are examined with particular emphasis on the hydrogeological and geotechnical conditions which made possible their continuous function throughout the centuries up today. In particular, the sustainability of the Hymettos and the Hadrianic aqueducts is investigated and attributed to the capture of underground water and the skillful construction of the tunnels. The geometry of the Hadrianic aqueduct and the situation in the ancient tunnel are presented based on data obtained during the resumption of the ancient work in the 19th and 20th centuries. The up to forty meters deep wells along the tunnel continue to collect underground water at many places along the twenty kilometers long path of the Hadrianic aqueduct. Similarly, the Hymettos aqueduct still irrigates the National Garden with a daily rate of about one thousand cubic meters. The stability of the ancient tunnels is correlated with the surrounding geological formations; it turns out that the stability problems of the ancient tunnels are comparable to those met in the tunneling works of the Metro lines, particularly in the Athenian Schists. A new part of an ancient aqueduct was crossed during the Metro works which is considered to belong to the Hymettos aqueduct.